2005
DOI: 10.1634/stemcells.2005-0170
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Nanofibrillar Surfaces Promote Self-Renewal in Mouse Embryonic Stem Cells

Abstract: The regulation of mouse embryonic stem cell (mESC) fate is controlled by the interplay of signaling networks that either promote self-renewal or induce differentiation. Leukemia inhibitory factor (LIF) is a cytokine that is required for stem cell renewal in mouse but not in human embryonic stem cells. However, feeder layers of embryonic fibroblasts are capable of inducing stem cell renewal in both cell types, suggesting that the self-renewal signaling pathways may also be promoted by other triggers, such as al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(101 citation statements)
references
References 58 publications
2
98
0
1
Order By: Relevance
“…We note that other approaches, both based on matrices [5,41] and molecular [36,38] approaches have been presented. The matrix approach described here is particularly flexible, and moreover may be useful in investigating Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We note that other approaches, both based on matrices [5,41] and molecular [36,38] approaches have been presented. The matrix approach described here is particularly flexible, and moreover may be useful in investigating Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These biologically derived materials are also very complex and are not subject to control at the molecular level. Synthetic hydrogel and fibrillar matrices have been explored, in an attempt to replace such complicated biological materials with defined artificial materials for short-term ESC culture [4,5], yet these materials still do not present the fullness of the ECMs repertoire of molecular characteristics. Sophisticated photochemical degradation approaches have been developed to explore the dynamic nature of cell-material interactions in the niche in artificial systems, for example the factors controlling stem cell chondrogenic differentiation [6].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, most studies with synthetic substrates and stem cells are largely concerned with their differentiation (reviewed in Lutolf & Hubbell, 2005). The first report of such a scaffold being used for undifferentiated culture of ESCs comes from Nur-E-Kamal, Ahmed, Kamal, Schindler, and Meiners (2005) who have recently used a commercially available synthetic polyamide matrix (UltraWeb) for the growth of mouse ESCs. The authors showed that proliferation and self-renewal, as well as Nanog expression, were enhanced relative to 2D surfaces and suggested that dimensionality may play a role in 'stemness' in mESCs.…”
Section: Other Substratesmentioning
confidence: 99%
“…Several cells types, including osteoblasts 78,79 , fibroblasts 80,81 , rat kidney cells 80 , smooth muscle cells 82 , neural stem cells 83 and embryonic stem cells 84 , have shown increased attachment on various nano-fibers compared to their corresponding control materials. Additionally, a recent study found that branched nano-fibers improve fibroblast attachment over linear nano-fibers 85 .…”
Section: Attachment and Proliferationmentioning
confidence: 99%